FOOD PREFERENCE AND CONSUMPTION OF AQUATIC MACROPHYTES SUBMERGED BY SNAIL Pomacea canaliculata - CRUZ,C. (2015)
ABSTRACTThe objective of this study was to evaluate the consumption potential, food preference and use of snail Pomacea canaliculata as a biocontrol agent of four submerged aquatic macrophytes (Ceratophyllumdemersum, Egeriadensa, Egerianajas and Hydrilla verticillata). Two experiments were performed. In the first experiment, the introduction of a snail took place and 10 grams of each macrophyte in plastic containers with 1 liter of water. The assessments of consumption by the snail were performed at each 48 hours, during 12 days. The second experiment was performed in 600 liters microcosms containing five snails in each experimental unit. Fifty grams of each macrophyte were offered the snails at the same time, adding the same amounts after seven, 14, 21 and 30 days. On both trials, the most consumed macrophyte by the P.canaliculata was H.verticillata (7.64 ± 1.0 g 48 h and 50 ± 0.18 g) respectively, significantly differing from the others. However, in the absence of H.verticilata, E.najas and E.densa were consumed. The preference of P.canaliculata for H.verticillata is very interesting, because this plant is exotic and problematic in Brazil, and the snail is one more tool for biological management of submerged aquatic macrophyte H.verticillata.